Anticancer Studies of Extracts and Fractions of Hertia Intermedia - Hakeemullah; Anwar, Muhammad; Khan, Jahangir; Inayatullah; Khan, Naqeebullah; Hakeem, Abdul (Al-Nahrain Journal of Science, 2020)
This study was conducted to prepare the extract from medicinal plant Hertia intermedia and its evaluation for presence of anticancer activity. The medicinal plant was collected and shade dried then crushed to convert it into powdered form. The powdered form of the plant was soaked for 15 days in an organic solvent methanol (CH3OH). The extract obtained passed through the filtration process followed by vaporization of the residual solvent using rotary evaporator. The methanol extract of Hertia Intermedia was used to prepare different fractions of solvent using aqueous dichloromethane, benzene, butanol, chloroform, ethyl acetate and n-hexane. Methanol extract, aqueous extract, butanol extract and extract of Hertia intermedia did not show any activity against cancerous cell lines. Hertia intermedia did not show any noticeable activity and remains inactive ROS against HeLa cell line, 3T3 cell line, MCF-7 cell line (cancerous cell). Hertia intermedia did not contain any bioactivity against cancerous or reactive oxygen species which is the initiator or producing cancer.